The use of an 8-week mixed-intensity interval endurance-training program improves the aerobic fitness of female soccer players - Clark, J. E. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study is to examine improvements in cardiorespiratory fitness (VO2) after the use of a mixed-intensity interval endurance-training (MI-ET) program in female soccer players, to validate the MI-ET program as an appropriate training regimen to improve cardiorespiratory fitness (VO2) in soccer players. 32 female soccer players (average 18.66 ± 0.31 years) were recruited from a group of currently conditioning local U-19 and college soccer teams and randomly assigned to participate in an 8-week periodized training program that involved either the MI-ET program or the continuation of a current endurance-training (ET) program. Analysis of variance indicates no differences in VO2 values within the group of athletes before participating in the exercise program. After the 8 weeks of training, the MI-ET group of athletes had significantly greater average VO2 values (62.13 ± 0.96 ml O2/kg·min vs. 57.27 ± 1.59 ml O2/kg·min), p = 0.015, along with a greater group average of change in VO2 (12.44 ± 0.92 ml O2/kg·min vs. 7.72 ± 0.99 ml O2/kg·min), p < 0.001. The MI-ET program is shown to be a valid means to improve aerobic fitness as indicated by the MI-ET group exhibiting significantly greater V?o2 measures after training.